Carta de Aptidão para a implantação de rodovias e avaliação de alternativas de traçado com uso de geotecnologias - Caetano, Norton Roberto [UNESP]; Ohara, Tomoyuki; Tavares de Mattos, Juércio [UNESP]; Jimenéz-Rueda, Jairo Roberto [UNESP] (My University, 2006)
This study discuss the use of the geotechnologies to aid the planners on the terrain aptness definition for highways implantation and on the different trace evaluation to the extention of the Governador Carvalho Pinto highway, between Taubaté-SP and Aparecida do Norte-SP. Fratures on the area were mapping using Landsat ETM+, band Pan. In order to elaborate the phisical aptness chart for highway implantation was used the Analitical Hierarchy Process (AHP) operation, in on geographical information system (GIS). Using GIS were realized a ponderate middle with the soils, rocks, relief, slope, fractures and land use/cover maps. Using this physical aptness chart and joinning it with urban and restrict areas (that was inserted by the Boolean operation), were obtained a viability chart for highway implantation. Based on it were proposed three aleatory traces for the Carvalho Pinto highway. This traces were evaluated with the cross tabulation operation. The integration of the restrict areas, land use and phisical aptness in digital media can offer for the planners the cartography of the viability for the highway implantation. The evaliation of these three traces, based on the viability chart, can subsidyse the decision by the planners.
Aptness chart for the highway implantation and evaluation of trace alternatives using geotechnologies
Keywords: Geographycal information system; Viability chart for the highway implantation; Geographic information systems; Insulating materials; Land use; Mapping; Maps; Planning; Boolean operations; Digital media; Geographical information systems; Hierarchy processes; Land use/cover; Landsat ETM+; Highway systems